Healthcare workers' structured daily reflection on patient safety, workload and work environment in intensive care. A descriptive retrospective study. (February 2022) - Larsson, Ing-Marie; Aronsson, Anna; Norén, Karin; Wallin, Ewa
Abstract: Objectives: To describe the results of use of structured daily reflection assessments among healthcare workers at an intensive care unit over the course of one year. Methods: In this descriptive retrospective study, data were analysed both quantitatively and qualitatively. The data encompassed 1095 work shifts, evaluated by healthcare workers at an intensive care unit using a structured daily reflection instrument. The areas evaluated were patient safety, workload and work environment, and free-text comments were possible. Findings: The results showed that 36% (n = 395) of work shifts, most of them daytime shifts (44%; n = 161), were affected. Workload was the area that affected most work shifts (29%; n = 309). Missed nursing care, complex care and inaccurate communication impacted patient safety, while patient care, multitasking and working conditions affected workload. Work environment was impacted by organisational factors, environment, lack of control and moral stress. Conclusion: Using daily reflection among healthcare workers in the intensive care unit illuminated areas that affect patient safety, workload, and work environment. The importance of communication and collaboration and how they can impact patient safety, workload, and the work environment were highlighted by the team.